PENGARUH PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI PEMEDIASI - Musabbihan, Nelly Agustina; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 7 No 4 (2018), 2018)
Firm value is the price that potential buyers are willing to pay when a company is sold. The value of this company is very important because it is a reflection of the company's performance that shows the prospects of the company in the future which is also a indicator of market valuation of the company as a whole. The purpose of this study is to determine the effect of profitability and dividend policy on firm value with capital structure as mediator. This research was conducted at Property and Real Estate Company listed on BEI. The number of samples taken as many as 14 companies from 42 companies listed during the period 2012-2016 with purposive sampling method. The analysis technique used is path analysis. Based on the results of the analysis found that profitability has a significant positive effect on capital structure, dividend policy has no significant positive effect on capital structure, profitability, dividend policy, and capital structure have a significant positive effect on firm value, and capital structure able to mediate between the effect of profitability on firm value but can not mediate the effect of dividend policy on firm value. Keywords: Profitability, dividend policy, capital structure, firm value